2017
DOI: 10.1002/chem.201605704
|View full text |Cite
|
Sign up to set email alerts
|

The A Priori Design and Selection of Ionic Liquids as Solvents for Active Pharmaceutical Ingredients

Abstract: Abstract:In this paper we derive a straightforward computational approach to predict the optimal ionic liquid (IL) solvent for a given compound, based on COSMO-RS calculations. These calculations were performed on 18 different active pharmaceutical ingredients (APIs) using a matrix of 240 hypothetical ILs. These results indicated that the 18 APIs could be classified into 3 distinct categories based on their relative hydrogen bond donating or accepting ability, with similar optimal IL solvent predictions within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…As shown in Figure , all the first peaks for anion‐ibuprofen RDFs are greatly sharper and higher compared with those of cation‐ibuprofen RDFs regardless of cation–anion combinations, which suggests that the anions primarily offer interaction sites to attract ibuprofen. This behavior is expected because ibuprofen is a Lewis acid and thus the interactions of ibuprofen with anions are much stronger than those with cations . Moreover, Figure a,d presents that the peak with the highest intensity of RDFs occurs at 1.8 Å for the [AcO] − and [TfO] − anions, while that for [BF 4 ] − and [PF 6 ] − anions locates at about 2.8 Å and 3.2 Å, respectively.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…As shown in Figure , all the first peaks for anion‐ibuprofen RDFs are greatly sharper and higher compared with those of cation‐ibuprofen RDFs regardless of cation–anion combinations, which suggests that the anions primarily offer interaction sites to attract ibuprofen. This behavior is expected because ibuprofen is a Lewis acid and thus the interactions of ibuprofen with anions are much stronger than those with cations . Moreover, Figure a,d presents that the peak with the highest intensity of RDFs occurs at 1.8 Å for the [AcO] − and [TfO] − anions, while that for [BF 4 ] − and [PF 6 ] − anions locates at about 2.8 Å and 3.2 Å, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…In another study, they found that the favorable solvation of lidocaine in imidazolium‐based ILs did not only result from the HB interactions between lidocaine and anions but also from the electrostatic interactions between lidocaine and cations, which was different from conventional experimental results that the cations played a negligible role . Furthermore, Myerson et al used COSMO‐RS calculations to demonstrate that both anions and cations form the HB interactions with the drugs, which were considered as one of the main contributing factors for the favorable solubility. In addition, Coutinho et al illustrated that the solvation mechanism of vanillin was observed to be most likely the formation of π–π interactions between vanillin and cations.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations